Evaluasi Faktor Penyebab Keterlambatan Bongkar Muat Batubara dan Strategi Penanganannya pada PT. Bahtera Adhiguna Cabang Merak: Penelitian - Meriah Kita Deliani; Heldina Selin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Maritime safety is a crucial aspect of maritime transportation, with ship seaworthiness as a key factor in ensuring safe operations. This study examines the procedures for issuing the Minimum Safe Manning Document (MSD) at the Class I Tanjung Balai Karimun Port and Port Authority (KSOP) as legal evidence of compliance with the minimum number and qualifications of ship crew members in accordance with national and international regulations. The study aims to describe the document issuance process, from submission, administrative verification, ship survey, to issuance by the port manager. The method used is field research through observation and library research of relevant regulations and literature, referring to national regulations and international conventions. The results of the study indicate that the procedures have been implemented in accordance with the provisions, although there are still obstacles such as delays in document completion, limited understanding of ship owners, and administrative issues. Overall, the Minimum Safe Manning Document plays an important role in ensuring ship seaworthiness, improving maritime safety, and providing legal certainty for ship operations.